Evaluasi Karakteristik Pemadatan Tanah Menggunakan Modified Proctor dengan Dua Metode Berbeda di Aceh Timur - Fara Qamara Elmyra; Jumelia Ardika; Yus Yudhyantoro; Cut Annisa Widya Sari Mastura (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Soil compaction is crucial in civil engineering as it affects soil shear strength, compressibility, and permeability, which determine infrastructure stability. Natural soils often have low bearing capacity, especially in clay layers, requiring thorough laboratory testing to identify appropriate compaction methods. This study compares the effectiveness of Modified Proctor tests using two procedures: Method A (No. 4 sieve) and Method C (3/4-inch sieve), applied to clay soil from Blan Nisam Village, Julok Subdistrict, East Aceh. Samples were taken from 7 points at the location with the assumption that the local soil is not homogeneous and will obtain representative data variations. Tests included Atterberg Limits, specific gravity, grain size distribution, and compaction per ASTM and SNI standards. Results classify the soil as A-6 (AASHTO) and CL (low to medium plasticity cay, USCS). Method C produced higher maximum dry unit weights which resulting a higher compaction value than Methode A. Meanwhile, Method A showed higher optimum moisture content with lower compaction value. Method C provides more large particles thus reducing the water requirement to achieve maximum density, which is the opposite of Method A testing. These findings confirm that soil compaction is highly sensitive to gradation and plasticity, impacting strength and permeability.